MLS Observations of Arctic Ozone Loss in 1996-97 - Manney, G. L.; Froidevaux, L.; Santee, M. L.; Zurek, R. W. (2004)
The Microwave Limb Sounder (MLS) observed ozone decreases in the Arctic Vortex beginning in January 1997 at 585K and in February 1997 at 465K.